Does vertical supervision enhance labor productivity? Evidence from China’s central environmental protection inspection - Weimin Xie; Jialu Guo; Hengxin Zhang; Mingxiao Fang (Humanities & Social Sciences Communications)
Abstract Vertical supervision is an important institutional arrangement for overcoming the principal-agent problem between central and local governments within political decentralization. This research employs panel data from Chinese A-share listed firms spanning 2012–2019, utilizing the Central Environmental Protection Inspection (CEPI) as an exogenous shock. Through the application of the staggered difference-in-difference approach, the study investigates the effect of vertical supervision on labor productivity. Our findings indicate that CEPI significantly promotes labor productivity. We identify three possible mechanisms driving this positive effect: increasing local government environmental governance’s willingness, intensity, and effectiveness. The analysis of heterogeneity indicates that the enhancing effect of vertical supervision on labor productivity is more pronounced within state-owned enterprises, regions characterized by lower resource dependency, and regions equipped with more robust environmental regulation. This study deepens our understanding of vertical supervision effectiveness in environmental governance and provides valuable insights for policymakers to improve regulatory frameworks.